2012
DOI: 10.18388/abp.2012_2198
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dietary supplementation with lutein diacetate and lutein: a pilot study of the effects on serum and macular pigment.

Abstract: Problem The responses of subjects taking a 20 mg/day lutein diacetate supplement were compared with that for a 20 mg/day crystalline lutein or a placebo. Methods Ten subjects, assigned to each of three groups, lutein diacetate (group 1), lutein (group 2), and a placebo (group 3), were supplemented for 24 weeks. Groups 1 and 2 consumed a dose equivalent to 20 mg per day of free lutein. Serum samples, collected at baseline, and at weeks 6, 12, 18, and 24 were analyzed by HPLC. Macular Pigment Optical Density (MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 14 publications
(16 reference statements)
0
18
1
Order By: Relevance
“…One of the major protective roles lutein has in the retina is to serve as an oxygen free radical scavenger during oxidative stress conditions. The ability of lutein to provide effective removal of free radicals, such as singlet oxygen particles, is primarily governed by the chemical structure of two hydroxyl groups acting as strong sinks for reactive oxygen species (Figure 2) [46,47,48]. Xanthophylls and carotenes are considered the most efficient singlet oxygen scavengers among the carotenoid families [49,50].…”
Section: Structure and Biochemistry Of Luteinmentioning
confidence: 99%
“…One of the major protective roles lutein has in the retina is to serve as an oxygen free radical scavenger during oxidative stress conditions. The ability of lutein to provide effective removal of free radicals, such as singlet oxygen particles, is primarily governed by the chemical structure of two hydroxyl groups acting as strong sinks for reactive oxygen species (Figure 2) [46,47,48]. Xanthophylls and carotenes are considered the most efficient singlet oxygen scavengers among the carotenoid families [49,50].…”
Section: Structure and Biochemistry Of Luteinmentioning
confidence: 99%
“…Few reports have been published about the response of the MPOD levels to lutein supplementation compared with each type of lutein (Landrum et al. ). Therefore, it remains unclear which type of lutein supplementation increases the MPOD levels.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Norkus et al (2010) reported that the serum lutein response was higher with free lutein than with lutein esters. Few reports have been published about the response of the MPOD levels to lutein supplementation compared with each type of lutein (Landrum et al 2012). Therefore, it remains unclear which type of lutein supplementation increases the MPOD levels.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a presumably differential solubility of zeaxanthin and zeaxanthin dipalmitate in the co-consumed dietary lipids might have also contributed to the enhanced bioavailability of the latter. However, previous studies on the influence of esterification on carotenoid bioavailability had reported only small effects (22)(23)(24) . For instance, in line with this finding, Chung et al (23) reported the post-prandial bioavailability of a single dose of a crystalline suspension of free lutein in oil (10•5 μmol/dose = 6 mg free lutein/dose) to be 10 % higher than that of a single dose of a crystalline suspension of mixed lutein esters in oil (9•8 μmol/dose equivalent to 5•5 mg free lutein/dose), although the difference did not reach statistical significance in only ten subjects (P > 0•05).…”
Section: Bioavailability Of Zeaxanthin Aggregatesmentioning
confidence: 91%